Extracts from Fermented Black Garlic Exhibit a Hepatoprotective Effect on Acute Hepatic Injury - Jen-Chieh Tsai; Yi-An Chen; Jung-Tsung Wu; Kuan-Chen Cheng; Ping-Shan Lai; Keng-Fan Liu; Yung-Kai Lin; Yu-Tsang Huang; Chang-Wei Hsieh (Molecules, 2019)
The mechanism of hepatoprotective compounds is usually related to its antioxidant or anti-inflammatory effects. Black garlic is produced from garlic by heat treatment and its anti-inflammatory activity has been previously reported. Therefore, the aim of this study was to investigate the hepatoprotective effect of five different extracts of black garlic against carbon tetrachloride (CCl4)-induced acute hepatic injury (AHI). In this study, mice in the control, CCl4, silymarin, and black garlic groups were orally administered distilled water, silymarin, and different fraction extracts of black garlic, respectively, after CCl4 was injected intraperitoneally to induce AHI. The results revealed that the n-butanol layer extract (BA) and water layer extract (WS) demonstrated a hepatoprotective effect by reducing the levels of alanine aminotransferase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), and hepatic malondialdehyde (MDA). Furthermore, the BA and WS fractions of black garlic extract increased the activity of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), glutathione reductase (GSH-Rd), tumor necrosis factor alpha (TNF-α), and the interleukin-1 (IL-1β) level in liver. It was concluded that black garlic exhibited significant protective effects on CCl4-induced acute hepatic injury.